Farinhada: construção simbólica na reprodução da agricultura familiar - Silveira, Maryane Meneses (2006)
This work deals with the tradition of knowing how to make flour, the farinhada , as a cultural heritage. It is an indigenous cultural heritage absorbed by the Portuguese during the Colonial Period and kept up till now as a cultural expression of the small farmers through the cassava transformation process, exchanging tradition and modernity. The space in study involved farinhadas occurred in the municipalities of Nossa Senhora de Lourdes, São Domingos, Malhador and Moita Bonita located in the state of Sergipe. It was observed that the practice of making flour reproduces the social and belonging relations since it is the domestic group who constructs the farinhada annually in a symbolic appropriation of the space of the casa de farinha (flour house). They gather together in a supportive way in order to produce flour and tapioca in rituals that alternate the work itself with songs and games, making this activity an enjoyable experience. In this context, it was verified that the farinhada is a cultural manifestation that, although with a resignificance, remains as an important practice to the familiar farming reproduction.